Chrysin, baicalein and galangin are indirect activators of the human constitutive androstane receptor (CAR). Issue 2 (4th March 2015) - Carazo Fernández, Alejandro; Smutny, Tomas; Hyrsová, Lucie; Berka, Karel; Pavek, Petr
Graphical abstract: Highlights: Galangin, chrysin, baicalein and baicalin do not interact with human CAR. Galangin, chrysin, and baicalein significantly repress EGFR-Tyr1068 autophosphorylation and signaling. TR-FRET coactivator assay and CAR assembly assay detect direct interaction with CAR. This study demonstrates the need for the testing of the direct CAR interaction of CAR activators. Abstract: The constitutive androstane receptor (CAR) is a crucial transcriptional regulator of key xenobiotic-metabolizing enzymes such as cytochrome P450 CYP3A4, CYP2C9 and CYP2B6. The flavonoids chrysin, baicalein and galangin have been reported to activate CAR and interfere with EGFR signaling. Nevertheless, it is not known if these flavonoids are direct CAR ligands or indirect phenobarbital-like CAR activators via the inhibition of epidermal growth factor receptor (EGFR) signaling. We analyze the interactions of chrysin, galangin and baicalein and its glycoside baicalin with human CAR. We have employed and validated methods that can study direct interaction with the CAR ligand binding pocket. Secondly, we determined if the compounds affect human EGFR signaling and interact with EGFR. Employing a TR-FRET coactivator assay with recombinant CAR or CAR assembly assay, a consistent activation of CAR with flavonoids and phenobarbital was not observed. It was determined, however, that galangin, chrysin, and baicalein may slightly repress EGFR-Tyr1068 autophosphorylation after EGF treatment, phosphorylation of downstream transcription factor ELK1 and stimulate EGFP–CAR nuclear translocation in primary human hepatocytes. These data suggest that flavonoids chrysin, galangin and baicalein are indirect human CAR activators. This study also demonstrates new approach how to test the direct CAR interaction with its ligands.